Improvement of cellulose-based water-retaining material by graft copolymerization of acrylonitrile and acrylic on microcrystalline cellulose - Piyanut Nakpong (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1993